Coupled aquaponics: Optimizing hydraulic retention times using a parallel unit process water treatment approach - Tetreault, Joseph; Fogle, Rachel L.; Fogarty, Sean; Guerdat, Todd (Frontiers in Horticulture, 2023)
Coupled aquaponics is the integration of recirculating aquaculture systems (RAS) and hydroponic cropping systems (HCS) into one system with shared culture water. Water conservation, revenue diversification, location-independent food production, and a reduced reliance on synthetically derived fertilizer salts have been identified as potential benefits of coupled aquaponic production. Despite these potential benefits, it has been difficult for producers to achieve success at the commercial scale. This review discusses how traditional linear coupled aquaponic system designs are not suited for intensive production due to a lack of scalability and water flow rate optimization to meet the differing requirements for finfish, vegetables, and water treatment with practices commensurate with the individual RAS and HCS industries. An alternative design for intensive coupled aquaponics is presented that utilizes a parallel unit process approach for independent hydraulic retention time optimization of each system component. The production benefits and scaling opportunities for each of the primary components in an aquaponics system are discussed. A review of recently published coupled aquaponics literature demonstrates that a system utilizing a parallel unit process design can result in more intensive fish production and a greater nutrient supply for plant production, leading to the potential for greater economic and space use efficiency.